2021
DOI: 10.3390/plants10040725
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Loci Responsible for Awn Development in Rice through Comparative Analysis of All AA Genome Species

Abstract: Wild rice species have long awns at their seed tips, but this trait has been lost through rice domestication. Awn loss mitigates harvest and seed storage; further, awnlessness increases the grain number and, subsequently, improves grain yield in Asian cultivated rice, highlighting the contribution of the loss of awn to modern rice agriculture. Therefore, identifying the genes regulating awn development would facilitate the elucidation of a part of the domestication process in rice and increase our understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Extensive studies of awn formation and elongation in rice revealed that awnless cultivars were established by sequentially selecting loss-of-function alleles or genes involved in awn formation and elongation during domestication (Amarasinghe et al 2020, Bessho-Uehara et al 2021). An-1 [also known as REGULATOR OF AWN ELONGATION 1 (RAE1); hereinafter referred to as An-1/RAE1] encodes a basic helix-loop-helix transcription factor expressed at the apex of the lemma primordia, which causes continuous cell division for awn elongation (Luo et al 2013, Furuta et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies of awn formation and elongation in rice revealed that awnless cultivars were established by sequentially selecting loss-of-function alleles or genes involved in awn formation and elongation during domestication (Amarasinghe et al 2020, Bessho-Uehara et al 2021). An-1 [also known as REGULATOR OF AWN ELONGATION 1 (RAE1); hereinafter referred to as An-1/RAE1] encodes a basic helix-loop-helix transcription factor expressed at the apex of the lemma primordia, which causes continuous cell division for awn elongation (Luo et al 2013, Furuta et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…qAwn2.2 is located close to qAWNL2 and An-4 (Amarasinghe et al 2020 ; Qin et al 2021 ). qAwn11.1 overlapped with an awn QTL on chromosome 11 (Bessho-Uehara et al, 2021 ). These co-locations of the known genes/QTLs detected in previous studies could provide proof of the accuracy of our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Some minor QTLs, qAWNL2 and An-4 , have also been detected using populations derived from interspecific crosses (Amarasinghe et al 2020 ; Qin et al 2021 ). Recently, a study explored the loci responsible for awn development in rice through a comparative analysis of all AA genome species (Bessho-Uehara et al 2021 ). Most known genes/QTLs for awn development were also detected, and two loci on chromosomes 7 and 11 were newly identified in that study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations